Evolving Statewide Transfer Policies: Persistent Efforts in a Climate of Workforce Development among Massachusetts Community Colleges - de la Torre Jr., Daniel; Wells, Ryan S. (Education Policy Analysis Archives, 2014)
Since their inception, community colleges have included the transfer function as a central mission, yet arguments have been made contending that two-year/community colleges have systematically diverted students toward occupational education and served to “cool out” students’ expectations for bachelor’s degrees. In the 21st century, community colleges continue to contend with multiple missions and identities. The diversionary discourse of cooling out continues to carry a lot of weight, especially when viewed from a workforce-development perspective stressing short-term employability as the primary community college objective. The two-fold purpose of this study focuses on the academic transfer mission of community colleges in a context where this mission has been in tension with, and often seemingly dominated by, the vocational mission. We utilize document and thematic analysis to identify the elements of formal transfer and articulation policies in the United States leading into the 21st century. Using these findings as a framework for comparison, we then draw on Massachusetts as a case study to explore how transfer and articulation policies have resembled and/or diverged from the components identified. We present implications in light of transfer policy development in Massachusetts, expanding discussion to stress the importance of common articulation guidelines within state-determined higher education priorities.